Synthesis and antiviral activity of a series of novel N-phenylbenzamide and N-phenylacetophenone compounds as anti-HCV and anti-EV71 agents - Jiang, Zhi (Acta Pharm Sin B, 2015)
A series of novel N-phenylbenzamide and N-phenylacetophenone compounds were synthesized and evaluated for their antiviral activity against HCV and EV71 (strain SZ-98). The biological results showed that three compounds (23, 25 and 41) exhibited considerable anti-HCV activity (IC(50)=0.57–7.12 μmol/L) and several compounds (23, 28, 29, 30, 31 and 42) displayed potent activity against EV71 with the IC(50) values lower than 5.00 μmol/L. The potency of compound 23 (IC(50)=0.57 μmol/L) was superior to that of reported compounds IMB-1f (IC(50)=1.90 μmol/L) and IMB-1g (IC(50)=1.00 μmol/L) as anti-HCV agents, and compound 29 possessed the highest anti-EV71 activity, comparable to the comparator drug pirodavir. The efficacy in vivo and antiviral mechanism of these compounds warrant further investigations.